2018
DOI: 10.1002/sim.7956
|View full text |Cite
|
Sign up to set email alerts
|

Combining multiple imputation and bootstrap in the analysis of cost‐effectiveness trial data

Abstract: In healthcare cost-effectiveness analysis, probability distributions are typically skewed and missing data are frequent. Bootstrap and multiple imputation are well-established resampling methods for handling skewed and missing data. However, it is not clear how these techniques should be combined. This paper addresses combining multiple imputation and bootstrap to obtain confidence intervals of the mean difference in outcome for two independent treatment groups. We assessed statistical validity and efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 39 publications
3
68
0
Order By: Relevance
“…However, we expect the intervals to be unnecessarily wide with M ¼ 1 because as shown by equation (6), with one imputation the estimator is subject to a relatively large amount of Monte-Carlo error. This is confirmed by the simulation results of Brand et al 11 ( Figure 1, panel C), which shows that the bootstrap percentile intervals were wider on average with M ¼ 1 compared with M ¼ 5. Moreover, their results suggested that coverage with M ¼ 1 was slightly above the nominal 95% level, which we investigate further in Section 4.…”
Section: Bootstrap Followed By MIsupporting
confidence: 82%
See 2 more Smart Citations
“…However, we expect the intervals to be unnecessarily wide with M ¼ 1 because as shown by equation (6), with one imputation the estimator is subject to a relatively large amount of Monte-Carlo error. This is confirmed by the simulation results of Brand et al 11 ( Figure 1, panel C), which shows that the bootstrap percentile intervals were wider on average with M ¼ 1 compared with M ¼ 5. Moreover, their results suggested that coverage with M ¼ 1 was slightly above the nominal 95% level, which we investigate further in Section 4.…”
Section: Bootstrap Followed By MIsupporting
confidence: 82%
“…Brand et al also found that the Boot MI percentile approach worked well in simulations. 11 They investigated it using either M ¼ 5 or M ¼ 1, and among the different combinations of bootstrapping and MI recommended using it with M ¼ 1. Provided the MI point estimator is consistent, we would expect the resulting confidence intervals to have correct coverage under uncongeniality or misspecification.…”
Section: Bootstrap Followed By MImentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in statistical significance will be tested using the Cochran-Mantel-Haenszeltest, taking stratification for the center into account. Bootstrapping will be combined with single imputation to account for uncertainty in the costeffectiveness outcomes and missing data in the utility and cost categories [28]. Also cost-effectiveness acceptability planes as well as cost-effectiveness acceptability curves will be presented, thereby graphing the probability that the TCZ strategy is costeffective compared to using the prednisone strategy as a function of willingness to pay.…”
Section: Secondary Endpointsmentioning
confidence: 99%
“…The variance surrounding the joint incremental costs and effects was characterised using non-parametric bootstrapping (1000 iterations), with multiple imputation (m = 5) nested within the bootstrap loops. 41…”
Section: Incremental Cost-effectiveness Analysismentioning
confidence: 99%